Landscape staging, representations, and landscape thinking in three touristified Shui villages in southern Guizhou (China) - Evelyne Gauche (Via@)
This contribution questions landscape representations amongst the Shui who live in Guizhou province (south China). This ethnic group, which has a strong specific cultural component, has seen its daily landscapes transformed by the implementation of tourist activities. The state-led growth of the tourist industry that started in rural areas during the early 1980s and reached Guizhou in the early 2000s has unfolded according to a highly standardized official scheme. Territories have been transformed drastically in order to set new landscape stages. In this context, the article highlights the way tourismification is changing the relationship between the Shui and their daily landscape, or more broadly, their milieu (to borrow the words of Augustin Berque). Tourism is now an integral part of this milieu through the hybridated representations of the landscape that have emerged from local residents, tourists, and the state.